PH homeostasis and cell signalling pathway reflected in capacitance relaxation phenomena. (14th July 2008) - Basak, T.K.; Ramanujam, T.; Halder, S.; Cyrilraj, V.; Ravi, T.; Kulshrestha, Prachi
In malignant cells, capacitance relaxation phenomena has been observed. This capacitance relaxation phenomena has been correlated with α dispersion and VEGF. It is interesting to note that, in the process of pH homeostasis, cell signalling pathway is modulated by NRF2 which reduces oxidative stress on cells. This reduction of oxidative stress reduces VEGF mRNA levels mediated through increase in intracellular GSH. These phenomena involving NRF2 signalling pathway and the status of VEGF which is correlated with the measurement of capacitance relaxation phenomena have been simulated in MATLAB 7.0.